Acyl-CoA synthetases as regulators of brain phospholipid acyl-chain diversity. (October 2020) - Fernandez, Regina F.; Ellis, Jessica M
Highlights: Phospholipid acyl-chain composition is highly diverse across tissues and cell-types. Membrane phospholipid acyl-chain composition affects cellular biological functions. Acyl-CoA synthetases (ACS) are potential master regulators of phospholipid acyl-chain diversity. ACS family of 26 enzymes each differentially regulate fatty acid metabolism. Abstract: Each individual cell-type is defined by its distinct morphology, phenotype, molecular and lipidomic profile. The importance of maintaining cell-specific lipidomic profiles is exemplified by the numerous diseases, disorders, and dysfunctional outcomes that occur as a direct result of altered lipidome. Therefore, the mechanisms regulating cellular lipidome diversity play a role in maintaining essential biological functions. The brain is an organ particularly rich in phospholipids, the main constituents of cellular membranes. The phospholipid acyl-chain profile of membranes in the brain is rather diverse due in part to the high degree of cellular heterogeneity. These membranes and the acyl-chain composition of their phospholipids are highly regulated, but the mechanisms that confer this tight regulation are incompletely understood. A family of enzymes called acyl-CoA synthetases (ACSs) stands at a pinnacle step allowing influence over cellular acyl-chain selection and subsequent metabolic flux. ACSs perform the initial reaction for cellular fatty acid metabolism by ligating a Coenzyme A to a fatty acid which both traps a fatty acid within a cell and activates it for metabolism. The ACS family of enzymes is large and diverse consisting of 25–26 family members that are nonredundant, each with unique distribution across and within cell types, and differential fatty acid substrate preferences. Thus, ACSs confer a critical intracellular fatty acid selecting step in a cell-type dependent manner providing acyl-CoA moieties that serve as essential precursors for phospholipid synthesis and remodeling, and therefore serve as a key regulator of cellular membrane acyl-chain compositional diversity. Here we will discuss how the contribution of individual ACSs towards brain lipid metabolism has only just begun to be elucidated and discuss the possibilities for how ACSs may differentially regulate brain lipidomic diversity.